lncRNA GAU1 Induces GALNT8 Overexpression and Potentiates Colorectal Cancer Progression - Xuemei Tang; Haoyu Ruan; Liu Dong; Sihan Li; Zhiyuan Wu; Ming Guan (Gastroenterology Research and Practice)
lncRNA is a key epigenetic regulator in biological processes. In the human cancer transcriptome library MiTranscriptome, we identified GAU1 as the top upregulated lncRNA in colorectal cancer (CRC) by sample set enrichment analysis (overexpression ranking percentile=99.75%, P<10−50), which is coexpressed with the potential oncogene GALNT8 (Spearman rho=0.67, P=2.44×10−23, TCGA dataset n=184). Experimental data revealed that GAU1 regulates the expression of GALNT8. The overexpression of either GAU1 or GALNT8 significantly promotes the cell cycle and proliferation of CRC cell lines and correlates with poor prognosis in patients with CRC (P=3.04×10−2), while silencing of GAU1 or GALNT8 suppressed the cancer cell proliferation and induced the CRC cell line resistance to oxaliplatin in vitro treatment. Our results suggested that the previously less studied GAU1 and GALNT8 may play as CRC prognosis markers and potential targets for chemotherapy treatment.